Bemarituzumab as first-line treatment for locally advanced or metastatic gastric/gastroesophageal junction adenocarcinoma: final analysis of the randomized phase 2 FIGHT trial. - TÜRK, HACI MEHMET; Wainberg Z. A.; Kang Y.; Lee K.; Qin S.; Yamaguchi K.; Kim I.; Saeed A.; Oh S. C.; Li J.; Turk H. M.; et al. (My University, 2024)
Background: We report the final results of the randomized phase 2 FIGHT trial that evaluated bemarituzumab, a humanized monoclonal antibody selective for fibroblast growth factor receptor 2b (FGFR2b), plus mFOLFOX6 in patients with FGFR2b-positive (2 + /3 + membranous staining by immunohistochemistry), HER-2-negative gastric or gastroesophageal junction cancer (GC). Methods: Patients received bemarituzumab (15 mg/kg) or placebo once every 2 weeks with an additional bemarituzumab (7.5 mg/kg) or placebo dose on cycle 1 day 8. All patients received mFOLFOX6. The primary endpoint was investigator-assessed progression-free survival (PFS). Secondary endpoints included overall survival (OS), objective response rate, and safety. Efficacy was evaluated after a minimum follow-up of 24 months. Results: In the bemarituzumab-mFOLFOX6 (N = 77) and placebo-mFOLFOX6 (N = 78) arms, respectively, 59.7% and 66.7% of patients were FGFR2b-positive in ≥ 10% of tumor cells. The median PFS (95% confidence interval [CI]) was 9.5 months (7.3-13.7) with bemarituzumab-mFOLFOX6 and 7.4 months (5.7-8.4) with placebo-mFOLFOX6 (hazard ratio [HR], 0.72; 95% CI 0.49-1.08); median OS (95% CI) was 19.2 (13.6-24.2) and 13.5 (9.3-15.9) months, respectively (HR 0.77; 95% CI 0.52-1.14). Observed efficacy in FGFR2b-positive GC in ≥ 10% of tumor cells was: PFS: HR 0.43 (95% CI 0.26-0.73); OS: HR 0.52 (95% CI 0.31-0.85). No new safety findings were reported. Conclusions: In FGFR2b-positive advanced GC, the combination of bemarituzumab-mFOLFOX6 led to numerically longer median PFS and OS compared with mFOLFOX6 alone. Efficacy was more pronounced with FGFR2b overexpression in ≥ 10% of tumor cells. Confirmatory phase 3 trials are ongoing (NCT05052801, NCT05111626).
Keywords: Bemarituzumab; Gastric cancer; FGFR2b; Targeted therapy; mFOLFOX6